HUBUNGAN INTENSITAS KEBISINGAN DENGAN TEKANAN DARAH SISTOLIK DAN DIASTOLIK PADA PEKERJA PERTAMBANGAN PASIR DAN BATU PT. X ROWOSARI, SEMARANG - Martyna Widya; Onny Setiani; Hanan Lanang Dangiran (Jurnal Kesehatan Masyarakat (Undip), 2018)
Noise can affected human health. Industrial noise with high intensity and prolonged exposuretincreases the risk of hypertension. The noise level in the sand and rock mining area PT. X was measured 88.3 dB(A). This studytaimed to analyzedtthe associationtbetweentthe intensity oftnoise andtblood pressuretin sand and rock mining workers PT. X Rowosari, Semarang. Thistwas antobservational researchtwith crosstsectionaltdesign, totaltsample was 31tpeople. This research was conducted at subdistrict Rowosari, Semarang City with research instrument as a questionnaire to interview personal characteristic, sound level meter to measure noise and digital sphygmomanometer to measure blood pressure before and after work. Datatweretanalyzed usingtChi Squarettest at α = 5%. Thetresults showedtthat 18 people (58.1%) had increasedtsystolictblood pressuretand 19tpeople (61,8%) had increasedtdiastolictbloodtpressure. There was an associationtbetween noisetintensity andtsystolic bloodtpressure (p = 0.017; RP = 3.273; 95% CI = 0.93-11.4). There were no associationtbetween noisetintensity andtdiastolic bloodtpressure (p =t0.253; RPt= 1.534; 95%tCI =t0.70-3.36). There were no association between working period and systolic blood pressure (p = 0.972, RP = 1,135, 95% CI = 0.6-2.11) and diastolic blood pressure (p = 0.252; RP = 0.650; 95% CI = 0.37- 1.12). There was no association between prolonged exposure with systolic blood pressure (p = 0.701, RP = 1.238, 95% CI = 0.61-2.50) and diastolictblood pressure (p = 0.697; RP = 0.816; 95% CI = 0.47- 1.41). The conclusion of this study, there is antassociation betweentnoise intensitytand systolic bloodtpressure on sandtand rock mining workers at PT. X Rowosari, Semarang.